NILAI TAMBAH PRODUK PERSUTRAAN ALAM DARI PRODUK INTERMEDIATE KOKON KE PRODUK AKHIR BENANG DI KELURAHAN WALANNAE KECAMATAN SABBANGPARU KABUPATEN WAJO - Andi Haruna (Jurnal Eboni, 2021)
This research aims to count the sericulture farmers income from the intermediate cocoon until the final product (raw silk). This research was conducted from April to May 2015 at Wallanae, Sabbangparu, Wajo Regency. Population and sample used were sericulture farmers and silk reelers has been determined purposively within 14 sample of the farmers and silk reelers with the exact same amount. Data was collected by direct observation in the research venue along with the farmers themselves and the interview obtained by questionnaire distribution and within the related institutes for this research. Result of the research showed that farmers income from cocoon is in the average of Rp.2.383.969 aech household annually, farmers income from yarn is in the average of Rp.8.004.500 each household annualy. Additonal value of the silk products from intermediate cocoon production to final producti of yarn which earned as much as Rp. 5.620.531 per household annually and Rp.78.687.430. annually. Those amount is obtained from selling raw silk as much as Rp.112.063.000 annually reduced with the number of raw materials from as much as Rp.3.337.557 annually.